Identical EP300 variant leading to Rubinstein–Taybi syndrome with different clinical and immunologic phenotype. Issue 7 (9th March 2022) - Saettini, Francesco; Fazio, Grazia; Bonati, Maria Teresa; Moratto, Daniele; Massa, Valentina; Di Fede, Elisabetta; Castiglioni, Silvia; Marchetti, Daniela; Chiarini, Marco; Sottini, Alessandra; Iascone, Maria; Cazzaniga, Giovanni; et al.
Abstract: The Rubinstein–Taybi syndrome (RSTS) is a rare developmental disorder characterized by craniofacial dysmorphisms, broad thumbs and toes, intellectual disability, growth deficiency, and recurrent infections. Mutations in the cyclic adenosine monophosphate response element‐binding protein (CREB)‐binding protein ( CREBBP ) or in the E1A‐associated protein p300 ( EP300 ) genes have been demonstrated in 55% (RSTS1) and up to 8% of the patients (RSTS2), respectively. Dysfunction of immune response has been reported in a subgroup of individuals with RSTS. Here we characterize two patients carrying the same EP300 variant and distinctive RSTS features (including congenital heart abnormalities, short stature, feeding problems, and gastroesophageal reflux). Whole exome sequencing did not support a dual molecular diagnosis hypothesis. Nonetheless, patients showed distinct clinical manifestations and immunological features. The most severe phenotype was associated with reduced T‐cell production and diversity. This latter feature was confirmed in a control group of four RSTS patients.